Una nueva especie de Eulaema de Costa Rica (Hymenoptera, Apoidea) - J. S. Moure, CmF (1963)
The author presents a short key to the genera of Euglossini of the Central American area including Panamá, and a key to the species of the genus Eulaema of the same geographical area. A new species, Eulaema (Apeulaema) willei is described from Costa Rica. This species resembles B. tropica (Linnaeus) but can be easily distinguished by its shorter malar area and shorter distance from the lower lateral comer of clypeus to the orbit, by the darker wings mostly on the radial and first submarginal ceUs and costal border of the marginal cell, and by the mixture of black and yellow hairs on the basal two fifths of the second terg, margins and lateral portions of the second to fourth terga and mostly of the two last terga and on the sterna.